Role of the rumen in copper and thiomolybdate absorption - Gould, L.; Kendall, Nigel R. (Cambridge University Press, 2011)
The rumen is the site of significant interactions between Cu, S and Mo. It also shows reactions between Cu, S and Fe. The interaction between Mo and S results in the formation of thiomolybdates, which in the absence of adequate quantities of rumen Cu are absorbed into the animal and bind to Cu in biological compounds. This is the cause of thiomolybdate toxicity, often misleadingly called Cu deficiency. The effects of thiomolybdates being absorbed into the animal are considered, especially how thiomolybdates bind to Cu-containing compounds such as enzymes, decreasing their activity without removing the active Cu component. The sources of Cu, Mo, Fe and S are examined, including the impacts of water and soil on the animal's intake. Within the present review we have been able to provide evidence that: all classes of thiomolybdates are formed in the rumen; in the absence of available Cu all thiomolybdates can be absorbed into the animal rapidly though the rumen wall or via the small intestine; thiomolybdates bind to Cu in biological compounds and are able to cause problems; effects of thiomolybdate are reversible in vivo and in vitro on cessation of thiomolybdate challenge; the tetra-thiomolybdate form is the most potent Cu binder with decreased potency with decreasing S in the compound. Fe will exacerbate a thiomolybdate problem but will not directly cause it.